2021
DOI: 10.1123/apaq.2020-0077
|View full text |Cite
|
Sign up to set email alerts
|

Time−Motion Characteristics and Physiological Responses of Para-Footballers With Cerebral Palsy in Two Small-Sided Games and a Simulated Game

Abstract: This study compared physical performance in a group of international cerebral palsy football players during two formats of small-sided games (SSGs) and performance in a simulated game (SG) according to players’ sport classes (FT1, FT2, and FT3). Internal load (heart rate and rating of perceived exertion) and external load (total distance, distance covered at different velocities, maximum speed reached, acceleration, and deceleration) were obtained with global positioning system devices during two formats of SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Possibly, due to the functional differences between classes and despite the lower external load of FT1 and FT2 (more affected classes) than FT3, the internal load or the perceived exertion could be similar following a match. These results show that the player sport classes with more impairment, despite having a lower physical response than the more functional profiles, have a similar perceived perception effort [10]. Therefore, it would be interesting to quantify in CPFPs not only the external match response but also the internal or perceived load, because this could provide complementary match load information.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Possibly, due to the functional differences between classes and despite the lower external load of FT1 and FT2 (more affected classes) than FT3, the internal load or the perceived exertion could be similar following a match. These results show that the player sport classes with more impairment, despite having a lower physical response than the more functional profiles, have a similar perceived perception effort [10]. Therefore, it would be interesting to quantify in CPFPs not only the external match response but also the internal or perceived load, because this could provide complementary match load information.…”
Section: Discussionmentioning
confidence: 90%
“…The present results showed no significant differences between sport classes in the RPE-ML and RPE. In this regard, Henríquez et al [10] found no differences between the sport classes in the RPE and the heart rate of CPFPs following the performance of two small-sided games and a simulation match, reinforcing the possibility that the mentioned factors may explain the absence of differences in the internal load across functional profiles. Contrary to the obtained results, previous studies observed differences in the external load of players' sport classes during international matches, showing the influence of the impairment profiles on physical response parameters [3,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A maioria dos estudos (n = 18) se propôs a realizar avaliações físicas e desempenho (Coswig et al, 2019;Daniel et al, 2020;de Freitas et al, 2020;Gamonales et al, 2019;Gorla et al, 2019;Henríquez et al, 2021;Henriquez et al, 2020;Moreira et al, 2017;Peña-González et al, 2021;Reina et al, 2016Reina et al, , 2017Reina et al, , 2018Reina et al, , 2019Reina et al, , 2020Rosch de Faria et al, 2018;Sarabia et al, 2020;Yanci et al, 2016Yanci et al, , 2018. Nesse sentido é possível observar que com relação ao desempenho, atletas de classes esportivas mais altas (FT3) apresentaram melhores resultados quando comparados com atletas de classes esportivas mais baixas (FT1), seja em testes de agilidade, altura de saltos ou testes de sprints.…”
Section: Avaliação Física E Desempenhounclassified